KESIAPAN STAIN PAMEKASAN DALAM MENYELENGGARAKAN PROGRAM MAGISTER MANAJEMEN PENDIDIKAN ISLAM - Qosim, Mohammad (STAIN PAMEKASAN, 2015)
This article describes STAIN Pamekasan readiness in organizing Islamic education master program especially the lecturer, literatures, infrastructure, prospect students, and curriculum. Data and findings showed that lecturer, literatures, infrastructure, prospect students, and curriculum conceptually ready in organizing Islamic Education Management master program.